Children’s rights to education: Islamic perspectives - Qanet, Ghulam Mohammad; Eishan Jan, Mohammad Naqib; Mohammad, Mohammad Tahir Sabit; Ahmad, Muhamad Hassan; Hasani, Rahmatullah (Serials Publications Pvt. Ltd., 2021)
This paper focuses on the children’s rights to education in Islam and evaluates its impact on their rights to education. Research findings specify that education in Islam is thought compulsory for all children in their childhood. Islamic sources distinguish among 'fardhu ‘ain' and 'fardhu kifayyah' sciences. The former is obligatory for all, while the latter is compulsory on some members of the Muslim community. Regrettably, this model is not given attention well for reasons ranging from plain ignorance and misinterpretations of the educations of Islam to the confusion of ethnic and cultural norms with the clear principles of Islam, among others.